Property of vertical aligned carbon nanotubes - Le, Thanh Tung. (2012)
Since its discovery, optical communication system has proved to be the best way to transmit data over long distance. The most noticeable feature of fiber is its high speed data transfer, less loss, immune to electromagnetic fields, which make the research on ultra short pulse generation crucial. One possibility to improve is using carbon nanotubes to modify the waveguide via evanescence filed. This project will investigate operating mechanism of optical fiber laser and fabricates the carbon nanotube-based optical devices which are implemented to facilitate the ultra-short pulse generation in the fiber lasers.